Motivasi Mahasiswa Keperawatan Tingkat Akhir Dalam Belajar Bahasa Inggris - Lotulung, Christa Vike; Purnawinadi, I Gede (Fakultas Ilmu Keperawatan Universitas Klabat, 2024)
This study aims to analyze the motivation to learn English among nursing students, especially in facing global competition. This study uses a quantitative-descriptive approach with 95 students selected purposively. Motivation to learn English is measured through two main aspects, namely integrative motivation and instrumental motivation. The results of the study indicate that instrumental motivation such as the desire to support a career and understanding popular culture content, are the main drivers for students in learning English. In addition, integrative motivation such as the desire to understand the culture of English-speaking countries and interact with native speakers, also has a significant role. Educational institutions are expected to develop English learning programs that are more applicable, oriented to the world of work, and based on the global needs of students. Further research is recommended to conduct an in-depth analysis of the factors that influence motivation, as well as a longitudinal approach to track changes in motivation along with the education process.